Actors, Access, Markets, and Values Involved in Oil Palm Expansion and Peatland Degradation in West Kalimantan, Indonesia - Ali Yansyah Abdurrahim; Arya Hadi Dharmawan; Soeryo Adiwibowo; Herry Yogaswara; Meine van Noordwijk (Forest and Society, 2025)
Despite numerous government regulations aimed at protecting Indonesia’s peatlands and surrounding communities, the rapid conversion of peatlands to oil palm plantations, coupled with associated fires, continues to cause severe environmental degradation and health-threatening haze that extends to neighboring countries. This study examines the political ecology of oil palm expansion and peatland degradation in the Pelang Peat Landscape, Ketapang, West Kalimantan, focusing on the period 2000–2021. By integrating spatial analysis with qualitative methods—including active participation, in-depth interviews, group discussions, and document review—this research uncovers the dynamics of land-use change and access mechanisms. Findings reveal that oil palm expansion has resulted in significant ecological degradation, particularly in Peat Ecosystem Protection (FLEG) zones, driven by hybrid access mechanisms that combine regulation-based (legal and illegal) and structural-relational strategies, such as financial capital, political authority, identity, and informal land markets. The study also identifies "astroturfing oil palm plantations" as a strategy by large corporations posing as cooperatives to bypass regulations, exacerbating degradation. Expansion patterns are categorized into three forms—centered, spotted, and dispersed—each shaped by actor motivations and capacities. Furthermore, the analysis highlights the interplay between instrumental values (profit-driven motives) and relational values (sustainability and community well-being), which underscores broader tensions in peatland governance. Regulatory incongruence further complicates enforcement, allowing actors to exploit legal ambiguities, perpetuating the "legal, but illegal" and "illegal, but legal" phenomena. These findings underscore the urgent need for integrated governance approaches that address ecological, social, and policy challenges in peatland management.